Genetic Characteristics of the Hemostasis System in Early Children with Pneumonia (Texas Journal of Medical Science, 2023)
The article presents information about the study of the features of the course of pneumonia in children, changes in the hemostasis system, features of genetic polymorphism in various inflammatory diseases. An acute inflammatory process in the lungs leads to a violation of their metabolic function, disrupts the balance of the hemostasis system of the lungs. According to the results of laboratory and instrumental examination in children with pneumonia, significant changes in the hemostasis system were revealed